Case study methodology in business research - Dul, Jan, 1954-; Hak, Tony (Chichester Ellis Horwood, 2008)
Case Study Methodology in Business Research sets out structures and guidelines that assist students and researchers from a wide range of disciplines to develop their case study research in a consistent and rigorous manner. It clarifies the differences between practice-oriented and theory-oriented research and, within the latter category, between theory-testing and theory-building.
Se descarga sin conexión desde el Discovery
Keywords: Gestión de empresas; Investigación -- Metodología; Libros electrónicos